2007
DOI: 10.3847/aer2007003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Astronomy Diagnostic Test

Abstract: Seventy undergraduate class sections were examined from the database of Astronomy Diagnostic Test (ADT) results of Deming and Hufnagel to determine if course format correlated with ADT normalized gain scores. Normalized gains were calculated for four different classroom scenarios: lecture, lecture with discussion, lecture with lab, and lecture with both lab and discussion. Statistical analysis shows that there are no significant differences in normalized gain among the self-reported classroom formats. Prerequi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 14 publications
1
25
0
2
Order By: Relevance
“…Given the biases introduced by various learning gains, caution must be taken when using these measures to draw conclusions about differences in science classroom performance across gender. Brogt et al [35] have shown that different expressions for calculating gains have different inherent biases, with Hake's normalized gain [36] being particularly sensitive to high pretest scores.…”
Section: Gainmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the biases introduced by various learning gains, caution must be taken when using these measures to draw conclusions about differences in science classroom performance across gender. Brogt et al [35] have shown that different expressions for calculating gains have different inherent biases, with Hake's normalized gain [36] being particularly sensitive to high pretest scores.…”
Section: Gainmentioning
confidence: 99%
“…Fourth, we use the absolute gain divided by twice the average of the two hg 2av i, which has been used before [35,39] to demonstrate the potential pitfalls of the estimator of choice. The equation used to calculate g 2av is given below; once absolute gains divided by twice the average of the two have been computed for each student, an average absolute gain divided by twice the average of the two hg 2av i can be calculated:…”
Section: Gainmentioning
confidence: 99%
“…While this study has drawn criticism since its publication, 18,19 it has no doubt shed light on the measurement of learning gains and the impact of various teaching methods. The normalized learning gain has been used as a measure of change in a variety of fields beyond physics, such as astronomy 20 and biology. 5 Others have recommended an analysis-of-variance-based approach to quantifying learning gains.…”
Section: ■ Methods Of Measuring Changementioning
confidence: 99%
“…If the students in the two classes are not similar, then our ability to measure learning improvement is somewhat compromised, since we are then comparing the effect of new a new teaching technique in classes that are different in the ability or preparation of the students. One can attempt to correct for differences between classes, but it cannot be done as cleanly; for example Brogt et al (2007) show that for some measures of learning gain, there can be a bias in the measured learning for different pretest scores. Table 2 lists the number of correct answers to each pretest question in 2006 and 2007.…”
Section: Assessment Testmentioning
confidence: 99%
“…Following the recommendation of Brogt et al (2007), we will use multiple statistical techniques to better test the validity of our results. Because this analysis assumes that the students in the 2006 and 2007 classes are drawn from the same populations, and is therefore subject to uncertainty from our somewhat ambiguous determination of this assumption, we decided to subject the data to a further test that used only the students in each year who answered incorrectly on the pretest.…”
Section: Correspondence Of Assessment Questions To Lab Activities Covmentioning
confidence: 99%